Formation of information competence of cadets of a military university - Natalia A. Lamukhina (Развитие образования)
The article substantiates the idea of the need for advanced professional training of cadets of a modern military university to meet the requirements for the information competence of an officer during the period of change in military-professional activity under the influence of informatization. The essence of the information perspective as a leading factor of influence determining the advance is revealed. The author's understanding of the structure of the officer's information competence in the aggregate of operational, subjective, axiological and reflexive components is presented. The process of forming the cadet's information competence is shown as a consistent change in the stages of solving the advanced professional task and achieving the expected results of professional and personal development: the stage of problematization, the stage of modeling, the stage of solution and the reflexive stage. The presented content, forms and methods of work that organize the process of forming the information competence of cadets are designed to ensure its integrity and effectiveness.